Analysis of the relationship between sex and prescriptions for guideline-recommended therapy in peripheral arterial disease, in relation to 1-year all-cause mortality: a primary care cohort study. Issue 3 (10th March 2022) - Benson, Ruth A; Okoth, Kelvin; Keerthy, Deepiksana; Gokhale, Krishna; Adderley, Nicola J; Nirantharakumar, Krishnarajah; Lasserson, Daniel S
Abstract : Objectives: To explore population patterns of sex-based incidence and prevalence of peripheral arterial disease (PAD), guideline-directed best medical therapy prescriptions and its relationship with all-cause mortality at 1 year. Design: A retrospective cohort study. Setting: Anonymised electronic primary care from 787 practices in the UK, or approximately 6.2% of the UK population. Participants: All registered patients over 40 with a documented diagnosis of peripheral arterial disease. Outcome measure: Population incidence and prevalence of PAD by sex. Patterns of guideline-directed therapy, and correlation with all-cause mortality at 1 year (defined as death due to any outcome) in patients with and without an existing diagnosis of cardiovascular disease. Covariates included Charlson comorbidity, sex, age, body mass index, Townsend score of deprivation, smoking status, diabetes, hypertension, statin and antiplatelet prescription. Results: Sequential cross-sectional studies from 2010 to 2017 found annual PAD prevalence (12.7–14.3 vs 25.6 per 1000 in men) and incidence were lower in women (11.6–12.4 vs 22.7–26.8 per 10 000 person years in men). Cox proportional hazards models created for PAD patients with and without cardiovascular disease over one full year analysed 25 121 men and 13 480 women, finding that following adjustment for age, women were still less likely to be on a statin (OR 0.69; 95% CI 0.66 to 0.72; p<0.001) or antiplatelet (OR: 0.87; 95% CI 0.83 to 0.90; p<0.001). Once fully adjusted for guideline recommended medical therapy, all-cause mortality was similar between women and men (adjusted HR (aHR) 0.95, 95% CI 0.87 to 1.03, p=0.198 for all patients, aHR 1.01, 95% CI 0.88 to 1.16, p=0.860 for those with cardiovascular disease). Conclusions: Women with a new diagnosis of PAD were not prescribed guideline-directed therapy at the same rate as men. However once adjusted for factors including age, all-cause mortality in men and women was similar.